Gestión operativa y su incidencia en la zona norte centro de emprendimiento de la prefectura de Los Ríos en el Cantón Quevedo, año 2021 - Perez Moran, Evelyn Gabriela (2022)
The present investigation was carried out in order to know the operational management and its incidence in the northern zone of the entrepreneurship center of the prefecture of Los Ríos in the Quevedo canton. The general objective is "Analyze the Operational management in the entrepreneurship center of the northern zone of the Los Ríos prefecture in the Quevedo canton, year 2021". The research has a mixed approach, it will focus on performing a data analysis through interviews and surveys to determine the situation on the operational management of the center, a Vester matrix and logical framework methodology will be used to present a proposal for improvement. The sample consisted of 15 collaborators and 100 entrepreneurs associated with the center. The results allowed us to know that within the entrepreneurship center, under the vision of its director, it maintains optimal operational management since they constantly seek continuous improvement, for which each of the processes is planned, however, it is evident that one weakness they have is a generalized budget planning where assigned values are not detailed for each item; Its collaborators consider that the operational management is excellent in 60%, being a negative aspect that it only receives training twice a year, and also that 40% of the activities destined to user service are only planned occasionally; The proposal was made using a Vester matrix to identify the central critical problem, and from this the logical framework matrix was applied, whose purpose is to improve the use and distribution of resources, time and supplies for the benefit of the center's users.